Quality and safety assessment of goat milk collected from different regions of Mathura city - Ojha, Sadhana; Pathak, Vikas; Goswami, Meena; Bharti, Sanjay Kumar; Singh, Tanuja (Indian Journal of Dairy Science, 2020)
The present study was carried out for quality and safety assessment of goat milk from five different regions of Mathura city viz. Holigate, Sadar, Aurangabad, Chungi and Township. The milk samples were collected from dairy shops, vendors and milk producers and evaluated on the basis of various organoleptic tests, physico-chemical properties, proximate estimation and microbiological studies following the standard procedures. Among organolpetic tests, Chungi (70%) and Township (90%) samples had clearer appearance than the other area. All sample collected from township is white in color. Regarding texture/consistency of milk, the sample procured from T having normal consistency and normal odor.Â The COB test was positive in 20 and 10% samples of H and S areas only. There was no significant difference in temperature, pH and titrable acidity of milk of different areas. However, the specific gravity showed significant (P<0.05) difference among milk samples from different regions. The specific gravity of S area samples was significantly (P<0.05) higher than H, C and T areas. The temperature, pH and specific gravity were lower however titrable acidity was higher than normal prescribed range in all milk samples. There was significant (P<0.05) difference for all proximate parameters except fat content. The moisture contents of H, C and T were significantly (P<0.05) higher but the SNF was lower than in S area. The protein percent of H region samples was significantly (P<0.05) lower than of other regions. The ash content of S region was significantly (P<0.05) higher than of C region, whereas total solid content of S region was significantly (P<0.05) higher than H, C and T region.Â The mean total solid content of A was comparable to C, H, T and S region. Although proximate parameters of goat milk deviated from normal prescribed range but all samples were negative for adulteration eg. preservatives, neutralizers and others adulterants. There was no significant difference in DMC, SPC, Coliform count and Staphylococcus count of milk samples collected from different regions however all samples had higher microbial load than the prescribed limit.